Physical Exercise Repairs Obstructive Jaundice-Induced Damage to Intestinal Mucosal Barrier Function via H2S-Mediated Regulation of the HMGB1/Toll Like Receptors 4/Nuclear Factor Kappa B Pathway - Shao, Changfeng; Li, Ye; Chen, Jiaqin; Zheng, Lan; Chen, Wei; Peng, Qi; Chen, Rui; Yuan, Afang (Frontiers in Physiology, 2022)
The present study aimed to determine the effect of aerobic exercise on improving damage to intestinal mucosal barrier function caused by obstructive jaundice (OJ) and explore the mechanism. Fifty male KM mice were divided into five groups: sham operation group (S), model group (M), exercise group (TM), DL-propargylglycine + exercise (PT) group, and sodium hydrosulfide + exercise (NT) group. Additionally, mice in S group underwent common bile duct ligation for 48 h to establish a murine obstructive jaundice model. In PT group, propargylglycine (40 mg/kg) was intraperitoneally injected 7 days after surgery. NaHS (50 μmol/kg) was intraperitoneally injected into mice in the NT group 7 days after surgery. The TM group, NT group and PT group exercised on a slope of 0% at a speed of 10 m/min without weight training (30 min/day). HE staining showed that the intestinal mucosa of group M was atrophied and that the villi were broken. The intestinal mucosal structure of mice in the TM group was improved. Serum assays showed that H2S levels were higher in the TM group than in the M group; compared with the levels in the TM group, the PT group levels were decreased and the NT group levels were increased. In addition, aerobic exercise inhibits the HMGB1/TLR4/NF-κB signaling pathway by promoting endogenous H2S production, thereby exerting a protective effect on the intestinal mucosal barrier.